Penguatan Kapasitas Aparatur dalam Pemetaan Wilayah Rawan Konflik di Lampung Tengah - Hutagalung, Simon Sumanjoyo; Hermawan, Dedy (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: Central Lampung Regency faces complex social challenges due to land disputes, ethnic differences, and economic inequality, which increase the risk of social conflict. The limited capacity of local government officials in identifying and mapping conflict-prone areas is a major obstacle to mitigation efforts. This study aims to enhance the capacity of local government officials in social conflict mapping to support evidence-based preventive policies. Methodology: The social conflict mapping training was conducted in three phases: preparation, implementation, and evaluation. Participants from various Regional Apparatus Organizations (OPD) were trained in conflict theory, mapping techniques, and data utilization for decision-making. The effectiveness of the training was evaluated through pre-tests, post-tests, and feedback questionnaires. Results: The training significantly improved participants' understanding and skills, with the average pre-test score of 60 increasing to 85 in the post-test. Feedback questionnaires indicated high appreciation for the relevance of the materials and interactive learning methods. Participant discussions successfully identified areas with high conflict potential and formulated mitigation strategies based on mapping. Conclusion: Training in Central Lampung effectively improved conflict mapping skills, with increased scores and calls for more practical sessions and sustained support. Limitations: The training was limited by its relatively short duration and constraints in GIS practice facilities. Additionally, the long-term effectiveness of this training has not yet been comprehensively measured. Contribution: This study contributes to improving the capacity of local government officials in social conflict mapping and provides recommendations for future training improvements.